MIX CULTURE INOCULANT PRODUCTION OF PHOSPHATE SOLUBILYZING AND INDOLE ACETIC ACID (IAA) PRODUCER RHIZOBACTERIA WITH AMBARAWA PEAT SOIL RAWAPENING AS CARRIER - Raharjo, Budi; Suprihadi, Agung (JURNAL SAINS DAN MATEMATIKA, 2010)
ABSTRACT—Plant production development is the main goals that do for increase the farming quality to fulfill the man needed in food. One of the ways is intensive farming, by using organic or inorganic fertilizer. Phosphate is the essential for plants. IAA is the necessary plant regulator for the root. Both phosphate and IAA need in plant growing and production. Biological fertilizer is fertilizer with microbial as the main material. Bacillus sp.DUCC-BR-K1.7, Bacillus sp. DUCC-BR-KI3, Bacillus sp.DUCC-BR-KI.2b and Pseudomonas fluorescens, Azotobacter chroococcum, Azotobqcter vinelandii, Azospirillum sp. and Azotobacter brazilensis are bacteria that can solubilization the phosphate and IAA synthesize. Those bacteria can be used as inoculants or biological fertilizer that put on carrier. One way to support the aim is giving the altemative carrier with suitable composition. The carrier should be support bacterial life during the storage. The aim ofthis research is find ths right consortia so can be used to optimized viabilities of culture Bacillus sp. DUCC-BR-KIJ, Bacillus sp. DUCC-BR-K1.3, Bacillus sp. DUCC-BR-KI.2b, P. flourescens, A. chroococcum, A. vinelandii, Azospirillum sp., and A. brazilensis in mix culture on peat soil as carrier. This research done in Microbiology Laboratory of Biology Department Diponegoro University. Subculture and activated culture in Nutrient Broth medium, make the growth curve to the biomass production, make the inoculums, prepare the peat soil, biomass production and mixed biomass with the carrier, enumeration bacterial culture viability test in carrier during the storage by TPC method. The results show that all consortia culture bacteria viabiliry Bacillus sp. DUCC-BR-KI.3 with Azospirillum (A) and Bacillus sp. DUCC-BR-K1.7, with P. flourescens (B) still viable and increasing number of population during seven weeks storage with l0 t-n CFU/g at To and up to l0 r3-ro CFU/g at the end storage. The consortium C between Bacillus sp. DUCC-BR-KI.2 b and A- brssilensis increasing the number of population and still viable during eight weeks storage (1013 - 1014 CFU/g).Key words: biofertilizer, peat soil, viability, mix cultare, consortiumPermalink : http://ejournal.undip.ac.id/index.php/sm/article/view/3138